City of love [videorecording (DVD)] - Boadella, Eric; Pattarini, Sara; Decesare, Robert; Schott, Kathryn; Nichols, Taylor (Freestyle Digital Media, 2023)
Spencer, a troubled ex-con, drives for a ridesharing company in Los Angeles to try to reconnect with the world after spending twenty years in jail, but quickly grows obsessed with one of his passengers.